Web-semp: método de elicitação, modelagem e planejamento para aplicações web - Zaniro, Dênis Leonardo (Universidade Federal de São Carlos, 2008)
Web applications differ from traditional applications in several significant ways, affecting the Requirements Engineering for Web (WebRE). The most WebRE methods proposed in the scientific literature are used in isolation and don t merge some of all practices and principles of Software Engineering. Besides, there aren t guidelines to tie up requirements specifications with conceptual design models and, at the same time, to support the construction of expressive models in such a way that they allow the metric application in the planning phase. Goal: based on this context, the goal of this work was to define a method, named Web-SEMP Web System Elicitation, Modeling and Planning proposed to help the elicitation, modeling and planning activities for Web applications. The proposed method defines both an approach to elaborate a conceptual model based on requirements, and a metric, named WHP Web Hypermedia Points to evaluate the size of Web applications. Method: the most quoted methods in the literature were analyzed aiming to reuse and to extend them to compose the method here proposed. From literature, the proposed method adopts both the AWARE and WebML techniques for elicitation and modeling activities, respectively, and the Use Case Points method for planning activity. Results: The Web- SEMP method was applied in the real development of a Web application and the results give insights of its contribution to conduct the WebRE process in a more systematic way. In order to evaluate the effectiveness of the WHP metric, it was applied in some implemented Web sites and the obtained results reflected, in proportional terms, the hours spent to develop them. Conclusions: According to the results, it could be observed that the Web-SEMP method enables to improve the quality of WebRE, and the WHP metric represents a first step towards more precise effort and cost estimation models.
Keywords: Ciência da computação; Engenharia de software; Sistemas web; Engenharia de requisitos; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO